Sensory-Driven Consumer Satisfaction in China’s Cigarette Market: A Structural Equation Model of Packaging, Taste, and Experience - Yang, Lei; Feng, Hong Tao; Hu, Hao Ruo; Li, Chao; Zhan, Jian Bo; Fan, Duo Qing; Tao, Ying; Wang, Jin; Jiang, Meng Fei; Zhang, Tao (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: In recent years, the Chinese cigarette market has undergone significant changes, with tobacco companies emphasizing consumer research in their product development and marketing strategies. A noticeable shift toward analyzing and optimizing the entire consumer experience makes a consumer-centric perspective the top priority in product development. Purpose: The study aims to create a consumer-centered evaluation system focusing on sensory and emotional aspects. Exploring the connections between packaging design, the smoking experience, quality perception, internal taste, innovative design, and product naming offers insights into leveraging these elements to differentiate products and improve brand competitiveness in a declining market. Design/methodology/approach: The study was conducted in 12 cities and involved quantitative research with a sample size of 2,521 participants. Participants were selected using stratified sampling to ensure representation from China's different geographical and economic regions. The analysis included the development of a structural equation model based on the relationships among seven latent variables and 62 observed variables. Findings/Result: This study shows that the smoking experience is the most critical factor in determining satisfaction, with internal taste playing a key role. Another result is that the packaging's tactile and auditory features, such as the smoothness of the box and the sound of tearing, significantly enhance the consumer experience. Sensory attributes, including aroma and visual appeal, greatly influence quality perception and overall satisfactionConclusion: This study provides new insights and empirical evidence for cigarette companies to better serve consumers, highlighting the role of sensory and emotional factors in product development and innovation.Originality/value (State of the art): By improving these influential indicators, cigarette products can effectively enhance their performance in the consumer journey experience. This paper provides a new perspective and empirical reference for cigarette enterprises to serve consumers better. Keywords: cigarette consumption experience, consumer satisfaction, sensory elements, influencing factors, structural equation model